Pengaruh Model Pembelajaran Super Brain Terhadap Hasil Belajar Matematika Siswa Kota Parepare - Rosnani Rosnani (Tautologi: Journal of Mathematics Education, 2023)
The background of this research is that, in the process of learning mathematics, students are less able to develop learning materials, this is evidenced by the average daily test scores of students who are still below the KKM value (75), one way to overcome this problem is to apply the super brain learning model. This study aims to determine that the application of the super brain learning model has a positive effect on mathematics learning outcomes for class VIII UPTD SMP Negeri 1 Parepare students. This type of research is an experimental research type. The variables studied in this study were the mathematics learning outcomes of class VIII UPTD SMP Negeri 1 Parepare as the dependent variable and the application of the super brain learning model as the independent variable.The population of this study were all students of class VIII UPTD SMP Negeri 1 Parepare for the academic year 2022/2023 which consisted of 10 (ten) classes. Sampling using probability sampling or cluster random sampling, from 10 classes one class was taken by lottery, namely class VIII.4 as the experimental class. The instrument used in this study was a validated learning outcome test. Based on descriptive statistical analysis, the average value of mathematics learning outcomes before applying the super brain learning model is 48.71 and the average value of mathematics learning outcomes after applying the super brain learning model is 77.10. Based on Inferential statistical analysis using One Sample t-test, a significant value was obtained, p = 0.000 = 0.05, this means that H0 is rejected and H1 is accepted. So it can be concluded that the application of the super brain learning model has a positive effect on mathematics learning outcomes in class VIII UPTD SMPN 1 Parepare students.